New Record of the Bottle Liverworts Sphaerocarpos Donnellii Aust. for Iraq and Middle East Countries - Al-Ni'ma, Basheer Ali Basheer (Iraqi Journal of Science, 2021)
The Order Sphaerocarpales of the bottle liverwort consists of five genera, among which Sphaerocarpos in turn consists of 8-9 species. The genus is nearly worldwide distributed, but disjunct, sporadic, and localized throughout the range in North America, South America, Europe, Africa, and Australia. According to the published checklist, only two species of Sphaerocarpos were recorded in the middle east countries. These are S. texanus and S. michelii, both were found in Turkey, while only the latter was found in Iraq. By the current study, an additional species, S. donnellii, will be added to the byroflora of the Middle East (south west Asia) region. A specimen of this species was found in Mosul city, Nineveh province, Iraq, grown on loamy soil in a house garden.